PSYCHOLOGICAL WELL-BEING ON CELEBRITY WORSHIP LEVELS IN EARLY ADULT KOREAN POP (K-POP) FANS - Priskylla Anindya Oktavinita; Krismi Diah Ambarwati (Jurnal Ilmiah Psyche, 2022)
Many K-Pop fans in Indonesia, especially early adults, could lead them to celebrity worship. Celebrity worship is the worship that fans do to their idol celebrity. One of the factors that cause celebrity worship behavior is the low level of psychological well-being. Psychological well-being (PWB) is individuals’ positive attitudes towards themselves and their social environment. This research is a quantitative study with simple linear regression analysis that aims to determine the effect of PWB on celebrity worship. This study used instruments the Ryff’s Psychological Well-Being Scales and the Celebrity Attitude Scales distributed through Google Form. The participants in this study were 378 members who joined one of the K-Pop groups on social media. The results showed that the significance value was 0,208>0,0005 (p>0,0005), so there was no significant effect between PWB on celebrity worship in early adults who like K-Pop. It concluded that the PWB does not affect the level of celebrity worship